Design and Build an RPG Game "Drop the Dragon" as a Medium for Practicing Mathematics Using the Finite State Machine Method - Mochamad Eza Foriansyah Foriansyah; Cindy Taurusta (Procedia of Engineering and Life Science, 2022)
Mathematics its one of the difficult subject to learned especially for a primary school children because they should be use the logical to understand the mathematics formula, that’s why the teacher must be a smart to use a right methods to teaching a mathematics and one of the right methods is can be used is a game media. Base on these problems, researches want to solve the problem with make a project research by making a desktop platform RPG Game used Unity3D application and using the FSM (Finite State Machine) methods, this game is designed and built by inserting a mathematics exam inside with the hope it can make a student easily to studies and learning mathematics with easily and happiness also interesting fiture in inside. The final result of this project is a RPG game by tittle “Jatuhkan naga” and can be used at computer platform.